The Limits of a Negative Interest Rate Policy (NIRP) - Gerhard Illing (Credit and Capital Markets – Kredit und Kapital, 2018)
The paper analyzes the experience with unconventional measures to cope with the Zero Lower Bound. It argues that forward guidance and quantitative easing are the natural extension of optimal monetary policy within the New Keynesian Framework, facing a Lower Bound. Unconventional policy had significant effects on financial variables and contributed to stabilizing the real economy. Negative rates have been successful in pushing the effective lower bound below zero. But given the risk of damaging side effects on financial stability and on central bank independence, these policy tools are likely to be less powerful and shorter-lived compared to standard tools. In view of the long-term decline of the natural rate of interest, raising the inflation target up to 3–4 percent appears to be the most promising way to relax the constraint imposed by the lower bound, providing a resilient buffer for effective stabilization. – – Die Arbeit untersucht die Auswirkungen unkonventioneller Geldpolitik. Sie zeigt, dass Forward Guidance und Quantitative Lockerung als Anwendung optimaler Geldpolitik im Rahmen Neu-Keynesianischer Modelle angesichts einer effektiven Zinsuntergrenze zu verstehen sind. Unkonventionelle Geldpolitik hat erfolgreich zur Stabilisierung von Finanzmärkten und Realwirtschaft beigetragen. Auch wenn sich die Zinsuntergrenze in gewissem Rahmen unter null senken lässt, ist die Wirkung unkonventioneller Maßnahmen – im Vergleich zu Standard-Instrumenten – jedoch kurzlebiger und weniger schlagkräftig, unter Berücksichtigung der Risiken für Finanzmarktstabilität und Zentralbankunabhängigkeit. Angesichts des nachhaltigen Rückgangs des "natürlichen" Realzinses erscheint eine Abhebung des Inflationsziels auf 2–4 % der geeignetste Weg, um einen robusten Mechanismus effektiver Stabilisierung zu erreichen.
Keywords: E43; E52; E58; 330; Natural rate of interest; unconventional monetary policy; zero lower bound; negative interest rate policy; inflation target; financial stability